Analogs of farnesyl diphosphate alter CaaX substrate specificity and reactions rates of protein farnesyltransferase. Issue 4 (15th February 2016) - Jennings, Benjamin C.; Danowitz, Amy M.; Wang, Yen-Chih; Gibbs, Richard A.; Distefano, Mark D.; Fierke, Carol A.
Graphical abstract: Abstract: Attempts to identify the prenyl-proteome of cells or changes in prenylation following drug treatment have used 'clickable' alkyne-modified analogs of the lipid substrates farnesyl- and geranylgeranyl-diphosphate (FPP and GGPP). We characterized the reactivity of four alkyne-containing analogs of FPP with purified protein farnesyltransferase and a small library of dansylated peptides using an in vitro continuous spectrofluorimetric assay. These analogs alter prenylation specificity and reactivity suggesting that in vivo results obtained using these FPP analogs should be interpreted cautiously.